2000
DOI: 10.1182/blood.v96.2.754
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged CD4 depletion after sequential autologous peripheral blood progenitor cell infusions in children and young adults

Abstract: Administration of mobilized peripheral blood progenitor cells (PBPCs) after high-dose chemotherapy rapidly restores multilineage hematopoiesis, but the ability of such products to restore lymphocyte populations remains unclear. In this report, we evaluated immune reconstitution in a series of patients treated with sequential cycles of high-dose chemotherapy, followed by autologous PBPC infusions (median CD34+ cell dose 7.2 × 106 cells/kg [range 2-29.3]). Although patients experienced rapid reconstitution of B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 23 publications
1
21
0
4
Order By: Relevance
“…Disease recurrence was frequent in our group. Recently, Mackall et al (2000) reported prolonged and profound CD4 + cell depletion after autologous PBPCT in children, which correlated with a high relapse rate and relatively high incidence of opportunistic and viral infections. Nordoy et al (1999) and Laurenti et al (2000) found persistent changes in immune function (including CD4 + cell depletion) as long as 4-10 years after autologous HCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease recurrence was frequent in our group. Recently, Mackall et al (2000) reported prolonged and profound CD4 + cell depletion after autologous PBPCT in children, which correlated with a high relapse rate and relatively high incidence of opportunistic and viral infections. Nordoy et al (1999) and Laurenti et al (2000) found persistent changes in immune function (including CD4 + cell depletion) as long as 4-10 years after autologous HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no large, single-centre comparison of immune recovery between paediatric recipients of autologous and allogeneic grafts. Studies in adults show faster T-cell recovery after autologous HCT (Shiobara et al, 1982), but some recent data suggest prolonged CD4 + T-cell depletion both in adults and in children post autologous HCT (Nordoy et al, 1999;Laurenti et al, 2000;Mackall et al, 2000).…”
mentioning
confidence: 97%
“…Cervical lymphadenopathy resolved 12 months after ASCT and the elevated anti‐CMV IgM titer normalized 6 months thereafter. Because recovery of the depressed CD4 + :CD8 + ratio after ASCT takes at least 1 year and because anti‐CMV drugs, such as ganciclovir and valganciclovir, could be toxic to newly engrafted hematopoietic stem cells, cautious follow‐up without anti‐CMV treatment should be considered for up to 1 year after transplantation in cases of post‐transplant localized CMV lymphadenitis without systemic involvement in patients with complete engraftment after ASCT. To the best of our knowledge, this is the first report to describe the pathologic findings and clinical course of CMV lymphadenitis without systemic involvement in a patient who had undergone ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…One major mechanism that may drive T cell dysfunction in MM patients is the profound lymphopenia induced during ASCT ( Figure 2 ). Immediately after ASCT, memory CD8 T cells are seen to expand disproportionately compared to CD4 T cells, 106–108 leading to a low CD4:CD8 ratio. In children and young adults, this ratio recovers to normal levels by 1 year post‐ASCT 108 but, in older adults, this ratio takes longer to recover, if at all 106,107 .…”
Section: Multiple Myelomamentioning
confidence: 99%
“…Immediately after ASCT, memory CD8 T cells are seen to expand disproportionately compared to CD4 T cells, 106–108 leading to a low CD4:CD8 ratio. In children and young adults, this ratio recovers to normal levels by 1 year post‐ASCT 108 but, in older adults, this ratio takes longer to recover, if at all 106,107 . There is also evidence that Treg cells expand disproportionately immediately after ASCT and remain high for prolonged periods 109 .…”
Section: Multiple Myelomamentioning
confidence: 99%